2008
DOI: 10.3892/ijo.32.2.425
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest and differentiation induction by 5,7-dimethoxycoumarin in melanoma cell lines

Abstract: Abstract. In the present study we investigated the antiproliferative activity of 5,7-dimethoxycoumarin on the murine B16 and human A375 melanoma cell lines. The inhibitory concentration 50 (IC 50 ) was estimated for each cell line by preliminary assay of tetrazolium salt reduction (MTT). With Trypan blue exclusion test we detected a cytostatic but not cytotoxic effect of the treatment in melanoma cells: 5,7-dimethoxycoumarin significantly reduced cell proliferation in a time-and dose-dependent manner, blocking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…The difference between the nutraceutical amounts found in commercial samples with respect to honeys produced in protected areas, suggested that foraged species can highly affect the content of antioxidant compounds present in bee product [34,35]. The presence of such bioactive molecules highlights the role of honey as nutritional source of natural antioxidants responsible for protecting human health, as reported by Schramm et al (2003) [36], Gheldof et al (2003) [37] and by McKibben and Engheseth (2002) [38]; moreover, studies conducted in our laboratory demonstrated the anti-proliferative activity of honey 5,7-dimethoxycoumarin in the B16 melanoma cell line [39]. Sometimes pesticides, veterinary substances and environmental contaminants, such as pesticides and heavy metals, may be present in non-negligible quantities in honey because they are accumulated by plants and automatically transferred to the bees through nectar and pollen [40][41][42][43].…”
Section: Discussionmentioning
confidence: 68%
“…The difference between the nutraceutical amounts found in commercial samples with respect to honeys produced in protected areas, suggested that foraged species can highly affect the content of antioxidant compounds present in bee product [34,35]. The presence of such bioactive molecules highlights the role of honey as nutritional source of natural antioxidants responsible for protecting human health, as reported by Schramm et al (2003) [36], Gheldof et al (2003) [37] and by McKibben and Engheseth (2002) [38]; moreover, studies conducted in our laboratory demonstrated the anti-proliferative activity of honey 5,7-dimethoxycoumarin in the B16 melanoma cell line [39]. Sometimes pesticides, veterinary substances and environmental contaminants, such as pesticides and heavy metals, may be present in non-negligible quantities in honey because they are accumulated by plants and automatically transferred to the bees through nectar and pollen [40][41][42][43].…”
Section: Discussionmentioning
confidence: 68%
“…Usually cell cycle arrest proceeds to either apoptosis or differentiation [21]. From the analysis of neuronal differentiation markers such as Map2, Gad67, heavy neurofilament we found that these drugs do not induce differentiation (data not presented), nevertheless, accumulation of cells in G1/S phase of cell cycle suggested activation of stress response.…”
Section: Curcumin Combination Inhibits the Stress Response Induced Bymentioning
confidence: 99%
“…Activation level of Erk 1/2 was analysed with its corresponding phospho-specific antibody. melanoma cell line, a strong melanogenesis process following 5,7-dimethoxycoumarin treatment was observed (11). In the present study, we investigated if the treatment affects melanogenesis in the human melanoma cell line as well (Fig.…”
Section: Inhibition Of Mek 1/2 Catalytic Activity In Melanoma Cells Umentioning
confidence: 99%
“…This molecule showed both a differentiating effect on HL-60 cell line (9) and an inhibition activity in DNA adduct formation, induced by carcinogens, in mouse mammary gland (10). Recently, our group investigated its antiproliferative activity on melanoma cell lines, including the murine B16 and human A375 lines (11). The 5,7-dimethoxycoumarin significatively reduced cell proliferation in a time and dose-dependent manner by blocking cell cycle in G 0 /G 1 , while cell growth inhibition was associated with the occurrence of cell differentiation.…”
Section: Introductionmentioning
confidence: 99%